The Margins versus the Centre of the National Literary Canon: The Reception of ‘The Legend of Master Manole’ in Romanian Education - Bartosiewicz-Nikolaev, Olga (Colloquia, 2024)
The main purpose of the article is to outline a panorama of the reception of ‘The Legend of Master Manole’ in Romanian education, from the beginning of its introduction to the Romanian national literary canon until the post-communist era. The paper explores how the discourse created around this text in the 19th century and perpetuated by interwar critics (e.g. George Călinescu, Mircea Eliade), and the ideology of protochronism during Ceaușescu’s regime, is preserved in post-communist textbooks. Although there have been some attempts at the feminist decanonisation of the ballad since 1989, they did not influence the main narrative presented in school manuals. The didactic literature still emphasises the male perspective of Manole, and his sacrifice for the act of creation, ignoring the perspective of Ana, the female character in the ballad, and her sacrifice. Starting from the premise that the canon is a certain set of beliefs which can be constantly engaged in polemics that should be continuously shaped and deconstructed, the article also proposes some new literary contexts in which ‘The Legend of Master Manole’ could appear in school textbooks.
Keywords: Romanian literary canon; Romanian didactic literature; ‘The Legend of Master Manole’; the legend of immured woman; feminist decanonisation